Towards more uniform conflict disclosures. (30th June 2010) - Drazen, Jeffrey M; Leeuw, Peter W de; Laine, Christine; Mulrow, Cynthia; DeAngelis, Catherine D; Frizelle, Frank A; Godlee, Fiona; Haug, Charlotte; Hébert, Paul C; Horton, Richard; Kotzin, Sheldon; Marusic, Ana; et al.
Abstract : The updated ICMJE conflict of interest reporting form